Politeness or Submissiveness: Forms and Functions of Politeness in Everyday Interactions within the Ndebele Society in Zimbabwe - Soneni Matandare (Journal of Communication and Cultural Trends, 2022)
In the traditional Ndebele society of Zimbabwe, there is a marked asymmetry of knowledge and authority between men, women, and children. It implies a difference in the application of negative and positive politeness by them based on their traditionally assigned gender roles. Hence, this study demonstrates how gender roles and relations within the Ndebele society influence the forms and functions of politeness used in daily interactions. The analysis was conducted by using the politeness theory as the theoretical framework, which proclaims that communication is a way that structures social relations. Personal and participant observations were used as sources of data collection. The research revealed that the forms and functions of politeness used in daily interactions within the Ndebele society are influenced by the formal and socially distant relationships between men, women, and children. In this regard, politeness conventions were determined by analyzing the norms, values, and particular power structures of the Ndebele society. Moreover, it was also found that gender dichotomy is developed from an early age and the “I” holds the power dynamics in relationships. So, it was concluded that the forms and functions of politeness in the Ndebele society are determined by one’s position in it. Furthermore, this position implicitly represents the social and power relations within the society, maintaining a patriarchal social structure and habitus. In this respect, the submissiveness of women towards their husbands shows the set pattern of the patriarchal society and its expectations from a woman.Keywords: gender roles, patriarchy, negative politeness, politeness, positive politeness, submissiveness